Effectiveness of video making to enhance infection control skills by undergraduate MBBS students - Tripathi, Purti C.; Singh, Himanshu R.; Suryawanshi, Rahul K. (International Journal of Clinical Trials, 2024)
Background: Competency-based medical education (CBME) Microbiology second MBBS curriculum, infection control practices are core competencies for certification of the second MBBS student. E-learning through video making can help students to achieve these infection control skills upto certifiable level. Educational videos which are of short duration, created in a step wise manner have shown to improve skill acquisition and augment observational learning. The aim and objectives were to study the effectiveness of video making as a teaching learning tool, to enhance infection control skills in undergraduate second MBBS students through video making and to evaluate the students’ infection control skills by giving them a prior checklist. Methods: Second MBBS students after taking informed consent were enrolled for the study. Ten infection control and prevention topics were included in the study for video making. All the 100 second MBBS students in 5 groups of 20 students had made all the 10 videos of duration 2 minutes. A self-administered, validated pre-test and post-test, multiple choice question (MCQ) test and objective structured practical examination (OSPE) checklist were used. Results: Mean post-test marks improved by a mean of 5.91 with significant p value (<0.001, using statistical package for the social sciences (SPSS) software version 29). Mean MCQ and OSPE scores also improved. In almost all the questions on feedback of student’s perception and assessment feedback, percentage of students who agreed and strongly agreed were far more than those who disagreed. Conclusions: Second phase MBBS students learning and performance of infection control skills greatly improved when they created their own videos.